Parenting Program to Increase Awareness of Early Childhood Care - Lily Sardiani Daulay; Masganti Sit; Ilham Karim Parapat; Nur Elmi (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research was conducted to determine the effectiveness of the parenting program "parent class" in increasing parents' awareness of early childhood care at Mutiara Zahra Kindergarten, Batang Kuis District, Deli Serdang Regency. This research is qualitative with a field study approach. The research was conducted at Mutiara Zahra Kindergarten, Batang Kuis District, Deli Serdang Regency. The research data is in the form of "parents class" activities given to parents at Mutiara Zahra Kindergarten. Data sources were obtained from the Principal and Parents. Observation, seminars, interviews, and documentation carry out data collection techniques. Data analysis is done by data reduction, presentation, conclusion, and verification. The study's results stated that the "parents class" activity conducted at Mutiara Zahra Kindergarten showed that the "parents class" activity could increase parents' awareness of Early Childhood Care.